Educational Supervision in the Era of Society 5.0 - Wahyul Huda (Universitas Negeri Semarang, 2023)
The lack of human resources in Indonesian education, especially the lack of professional educators and teachers to carry out the work, may be the reason for the country's low level of education. One way to improve the quality of education is the professionalization or pedagogical supervision of teachers. Supervision using a variety of methods can help address and improve educational problems by supporting, monitoring, guiding, and guiding educators to professionalism. The goal is to improve education and address related issues. Instructional supervision assists teachers in developing lesson plans that lead to desired learning outcomes. Supervision is an integral part of efforts to improve learning outcomes and teacher quality. Supervision or supervision is an attempt to serve education, especially teachers. Educational oversight is also the process of managing and evaluating all educational activities to ensure that they are carried out as planned. At the same time, it serves as a means of improving and correcting any deviations that may prevent you from achieving your goals. The aim is to investigate pedagogical oversight to enhance teacher professionalism. This article was written using a literature review methodology that includes a variety of literature sources related to research material management, reading and notation, and information gathering techniques. Some information is based on research studies.